Slag-metal interfacial reactions in pyrometallurgical processing of industrial wastes for recovery of valuable metals - H J. Kim; R R. Kim; H S. Park; J H. Park (The Australasian Institute of Mining and Metallurgy, 2024)
This study focuses on the recovery of valuable metals, specifically silver (Ag) and palladium (Pd), from copper-containing sludge (with copper content less than 20 per cent) generated during PCB processing and from spent petrochemical catalysts used in vapour decomposition during oil refining processes. The present results indicate that an increase in the mixing ratio of alumina-based spent catalyst leads to a decrease in the recovery rate of Ag and Pd. The recovery rates for Ag and Pd range from 84 per cent to 96 per cent and 80 per cent to 98 per cent, respectively. This trend is attributed to the increased emulsification of copper droplets containing Ag and Pd in the slag. The emulsification is caused by the decrease in the settling velocity of the copper droplets due to the increased viscosity of the slag as well as by the decrease in the slag-metal interfacial tension due to an increase in sulfur content at higher mixing ratio of spent catalyst.